2022
DOI: 10.3389/fped.2022.837247
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Model for Predicting the Clearance of Jaundice in Patients With Biliary Atresia After Kasai Procedure

Abstract: BackgroundThe failed clearance of jaundice (CJ) in patients with biliary atresia (BA) after the Kasai procedure (KP) often leads to a shorter native liver survival (NLS) time and earlier liver transplantation. We aimed to investigate risk factors of failed CJ and establish a novel nomogram model to predict the status of CJ.MethodsWe retrospectively reviewed institutional medical records from January 2015 to April 2020 and enrolled BA patients post-KP, randomly divided into training and testing cohorts at a rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Children with normal GGT levels received liver transplantation at a younger age and had a significantly lower native liver survival rate. Zhang et al (31) analyzed the correlation between preoperative GGT and postoperative COJ in 175 patients and found that low GGT was an independent risk factor for failure of postoperative COJ. As a whole, these results suggest that lower preoperative GGT levels may be associated with poor prognosis after KP.…”
Section: Discussionmentioning
confidence: 99%
“…Children with normal GGT levels received liver transplantation at a younger age and had a significantly lower native liver survival rate. Zhang et al (31) analyzed the correlation between preoperative GGT and postoperative COJ in 175 patients and found that low GGT was an independent risk factor for failure of postoperative COJ. As a whole, these results suggest that lower preoperative GGT levels may be associated with poor prognosis after KP.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Zhang et al, evaluated a nomogram to predict the clearance of jaundice post-KPE ( 53 ). They demonstrated that the AUCs of their nomogram were 0.96 and 0.91, respectively, in the training and validation cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the serum TP level is an important indicator that can reflect physiological function of the liver and nutritional status of human body. The lower TP level implies more severe fibrosis and weaker physical conditions, which are likely to influence the outcome of KPE.Previously, Zhang et al, evaluated a nomogram to predict the clearance of jaundice post-KPE(53). They demonstrated that the AUCs of their nomogram were 0.96 and 0.91, respectively, in the training and validation cohorts.…”
mentioning
confidence: 99%
“…Although KPE was developed more than half a century ago, a successful predictive model for precisely predicting response to KPE is lacking. Several potential clinical predictors (e.g., age, liver fibrosis, serum bilirubin levels) [10][11][12][13][14] and gene expressions 15,16 correlate with the prognosis of BA infants after KPE has been reported, but the predictive value of a single biomarker is limited. Previously, we built a clinical indicators-based nomogram that included age, 2DSWE, GGT, and APRI prior to KPE 17 to preoperatively predict the outcomes of KPE for BA patients.…”
Section: Introductionmentioning
confidence: 99%